Incidence of Hospitalized Stroke in the Czech Republic: The National Registry of Hospitalized Patients - Sedova, Petra; Brown, Robert D; Zvolsky, Miroslav; Kadlecova, Pavla; Bryndziar, Tomas; Kubelka, Tomáš; Weiss, Viktor; Volný, Ondřej; Bednarik, Josef; Mikulik, Robert (Journal of stroke and cerebrovascular diseases, 2017)
BACKGROUND: Contemporary stroke incidence data are not available in some countries and regions, including in Eastern Europe. Based on previous validation of the accuracy of the National Registry of Hospitalized Patients (NRHOSP), we report the incidence of hospitalized stroke in the Czech Republic (CR) using the NRHOSP. METHODS: The results of the prior validation study assessing the accuracy of coding of stroke diagnoses in the NRHOSP were applied, and we calculated (1) the overall incidence of hospitalized stroke and (2) the incidence rates of hospitalized stroke for the three main stroke types: cerebral infarction (International Classification of Diseases Tenth Revision, CI I63), subarachnoid hemorrhage (SAH I60), and intracerebral hemorrhage (ICH I61). We calculated the average annual age- and sex-standardized incidence. RESULTS: The overall incidence of hospitalized stroke was 241 out of 100,000 individuals. The incidence of hospitalized stroke for the main stroke types was 8.2 cases in SAH, 29.5 in ICH, and 211 in CI per 100,000 individuals. The standardized annual stroke incidence adjusted to the 2000 World Health Organization population for overall stroke incidence of hospitalized stroke was 131 per 100,000 individuals. Standardized stroke incidence for stroke subtypes was 5.7 cases in SAH, 16.7 in ICH, and 113 in CI per 100,000 individuals. CONCLUSIONS: These studies provide an initial assessment of the burden of stroke in this part of the world. The estimates of hospitalized stroke in the CR and Eastern Europe suggest that ICH is about three times more common than SAH, and hemorrhagic stroke makes up about 18% of strokes.
Keywords: lidé; mladiství; Adult; subarachnoidální krvácení; Hospitalization; Middle Aged; registrace; rozložení podle pohlaví; Age Distribution; Infant; Female; Sex Distribution; dítě; epidemiology; Stroke; Incidence; cerebrální krvácení; retrospektivní studie; registry; Adolescent; Humans; Infant, Newborn; Česká republika; subarachnoid hemorrhage; cévní mozková příhoda; Registries; předškolní dítě; Subarachnoid Hemorrhage; lidé středního věku; cerebrální infarkt; Child, Preschool; intracerebral hemorrhage; věkové rozložení; mužské pohlaví; mladý dospělý; hospitalizace; novorozenec; Time Factors; Czech Republic; ženské pohlaví; Young Adult; Aged, 80 and over; senioři nad 80 let; časové faktory; Aged; incidence; Male; Cerebral Hemorrhage; Retrospective Studies; Child; Cerebral Infarction; dospělí; kojenec; senioři